PENGUJIAN DAYA HANTAR LISTRIK AIR TANAH DI SEKITAR TEMPAT PEMBUANGAN AKHIR GUNUNG TUGEL KABUPATEN BANYUMAS MENGGUNAKAN PRINSIP JEMBATAN WHEATSTONE - Sehah Sehah; Wahyu Tri Cahyanto (Universitas Jenderal Soedirman, 2009)
Electrical conductivity of groundwater have been measured in area about the final garbage dismissal place (TPA) of Gunung Tugel, Regency of Banyumas. Groundwater samples have been taken away from 104 point of groundwater sources which distributed around of the research area, consisted of well water, belik water and pump water. Then, water samples are tested in Electronics and Instrumentation laboratory, Faculty of Science and Technique, UNSOED use the Wheatstone bridge principle. Electrical conductivity of groundwater obtained, then mapped pursuant to position of samples points location, so that obtained map of electrical conductivity contour of groundwater in research area. Pursuant to the electrical conductivity contour map, known that the mean electrical conductivity value in research area is 0,0594 kW-1, where highest electrical conductivity value is 0,1449 kW-1 and lowest electrical conductivity value is 0,0209 kW-1. Pursuant to interpretation known that most liquid waste (leacheat) of TPA Gunung Tugel are indicated flow into south and south-west area (Village of Kedungrandu) owning lower topography.